Management and Employee Perspective on Diversity: A Review Essay - Gondal, Muhammad Ali; Ullah, Sami (Journal of Asian Scientific Research, 2011)
The interest of employers about the issue of managing workforce diversity has grown rapidly. A number of articles and books have been written on this issue in almost all parts of the world but yet the findings of the researches are fragmented with respect to definition and ways to manage diversity. This review article on workforce diversity is arranged with respect to definition of diversity, managerial and employee perspective on diversity, diversity training programs, and the causes of failure of diversity training programs. Articles and books covering these aspects of diversity are reviewed in this regard. It is found that disparity in the managerial and employees perspective about the diversity is the main factor behind the failure of diversity training conducted in different parts of the world. Further it was found that the successful achievement of the objectives of diversity training programs, employers should incorporate the opinion of employee representatives.